Identifikasi Zona Rawan Banjir Menggunakan Sistem Informasi Geografis (Studi Kasus: Sub DAS Dengkeng) - Muhammad Dimas Aji N.; Bambang Sudarsono; Bandi Sasmito (Jurnal Geodesi UNDIP, 2014)
Dengkeng Sub Watershed is part of the Upper Solo River Basin which includes the area of the River Solo. Degradation of land and buildings open to residential areas but not done a good arrangement is the cause of the destruction of the Bengawan Solo River basin mainly upstream, resulting in the reduction of water resources in the area.This study aims to determine the extent and whichever area including flood prone areas and to determine the factors that cause flooding in DengkengSub Watershed. The methods that use in scoring and to overlay (overlapping stacking) method between the type of soil maps, land use maps, maps of slope, drainage network map and rainfall maps. Watershed maps obtained from the four overlay map. Identification of water recharge areas is done using a Geographic Information System (GIS) that can be used as a material consideration to conservation and rehabilitation the land and the forest.Remote sensing data used are Landsat images of 2012 were used for the manufacture of sub-watershed land use map Dengkeng in 2012 using ENVI 4.4. Rainfall map created using rainfall data 2001-2011 period and slope maps using data sub-watershed high point Dengkeng processed using ArcGIS 9.3.The results show the extent of each flood-prone zones in Sub watershed Dengkeng. From the results of extensive analysis of sub-watershed Dengkeng is 822,153 km². The area included in the zone not prone area of 3,349 km² (0,41%) and somewhat prone zones of 45,865 km² (5,58%). The area included in the zone quite prone area of 268,744 km ² (32,69%). For a very broad zone of cartilage and cartilage is 469,63 km ² (57,12%) and 34,567 km ² (4,20%).Keywords: Watershed, Geographic information system, Water recharge areas, Skoring, Overlay